Intraosseous polymorphous low-grade adenocarcinoma of mandible: A rare entity - Gayathri Ramesh; Ram Manohar; Vandana Raghunath; Ramesh Nagarajappa (Wolters Kluwer Medknow Publications, 2012)
Polymorphous low-grade adenocarcinoma is a rare type of minor salivary gland malignancy. The characteristic features of these tumors are the varied histomorphology and the malignant, albeit indolent behavior. It occurs commonly in the minor salivary glands, with the palate (58.5%) being the most common intra oral site. Maxillary area (2%), mandibular mucosal area (1.5%) and posterior trigone region (0.5%) are the least affected areas. An occasional case has been reported arising from an intraosseous location i.e the maxilla, and only two cases have been reported in the English literature originating from the mandible. One such very rare case of polymorphous low-grade adenocarcinoma of the mandible, which radiographically has a soap bubble appearance, is reported here.